IDIOMS WITH COMPONENT FACE IN THE TRANSLATIONS FROM CZECH INTO MACEDONIAN (Philological Studies, 2019)
In our presentation we will stress the semantics of somatic idioms with component ‘face’ both in Macedonian and Czech language, as well as the classification of possibilities for their translation from one language into another. We will analyze the problems arising during translation of idioms which can have pragmatic, language nature, culture-specific problems or problems arising from the specifics of the phrases themselves.
Keywords: Macedonian idioms, Czech idioms, face